Development of Folk Games as an Android-Based Game for Advancement Riau Malay Culture - Setiawan, Panji Rachmat; Syefriani, Syefriani; Wandri, Rizky; Pangestu, Firly Bagdja (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Indonesia is a heterogeneous country and has thirty-four provinces from Sabang to Merauke. There are many cultures in Indonesia. Every province has their different culture from others. One of the existing provinces in Indonesia is Riau province. Riau is a province that is located in Sumatera Island. Riau province has culture in folk games. A folk game is a game played traditionally that is owned by people and inherited to the next generation. Nowadays, the younger generation love to play alone using smartphone rather than played together in the folk game. So that the Author conduct research introduction to folk games to young generation by developed game that is played in smartphone, in this case is Android. Game introduces four folk games, which are adu biji para, statak, gasing, and congklak. All these folk games are found in Riau province. The game was developed using Game Development Life Cycle (GDLC) methodology that has six stages and every stage has output for the next stage. This research uses qualitative methodology in collected data that used in this research.